2017
DOI: 10.1155/2017/8214541
|View full text |Cite
|
Sign up to set email alerts
|

Roles and Mechanisms of Herbal Medicine for Diabetic Cardiomyopathy: Current Status and Perspective

Abstract: Diabetic cardiomyopathy is one of the major complications among patients with diabetes mellitus. Diabetic cardiomyopathy (DCM) is featured by left ventricular hypertrophy, myocardial fibrosis, and damaged left ventricular systolic and diastolic functions. The pathophysiological mechanisms include metabolic-altered substrate metabolism, dysfunction of microvascular, renin-angiotensin-aldosterone system (RAAS) activation, oxidative stress, cardiomyocyte apoptosis, mitochondrial dysfunction, and impaired Ca2+ han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 113 publications
1
36
0
Order By: Relevance
“…This further complicates the identification of the responsible mechanism(s). Recently, numerous studies have focused on Chinese herbal medicines and their impact on several diseases [ 19 22 ], however, their anti-inflammatory effects remain largely unknown. Thus, in the current study we analyzed ethanolic extracts of medicinal plants, which may have anti-inflammatory properties (see S1 Table in the supplementary data).…”
Section: Introductionmentioning
confidence: 99%
“…This further complicates the identification of the responsible mechanism(s). Recently, numerous studies have focused on Chinese herbal medicines and their impact on several diseases [ 19 22 ], however, their anti-inflammatory effects remain largely unknown. Thus, in the current study we analyzed ethanolic extracts of medicinal plants, which may have anti-inflammatory properties (see S1 Table in the supplementary data).…”
Section: Introductionmentioning
confidence: 99%
“…Among these natural products, Astragalus polysaccharides (APS) is one of the main active extract from Astragalus membranaceus (20,(22)(23)(24)(25)(26)(27). Previous studies showed that, for diabetic cardiomyopathy in hamsters, APS can induce myocardial collagen deposition and improve cardiac function by activating ERK1/2 signal pathway (23,28). Besides, APS can improve cardiac glucose metabolism dysfunction by inducing expression of GLUT-4 and inhibiting PPAR expressing (20,24,29).…”
Section: Introductionmentioning
confidence: 99%
“…25 However, many studies have found that some natural bioactive extracts have the pharmacological effect of treating diabetes-induced myocardial injury. 9 Our results showed that aer 6 weeks of gavage treatment with HED, there was no signicant difference in FPG levels between the db/db + HED mice and the db/db control mice. These results suggest that HED, which plays an anti-inammatory role, cannot be used alone as a hypoglycaemic drug.…”
Section: Discussionmentioning
confidence: 50%
“…8 However, studies have found that some bioactive natural compounds extracted from plants can directly inhibit inammation in diabetic hearts without lowering blood glucose levels. 9,10 Moreover, NF-kB, which plays a key role in the inammatory signalling pathway, is also involved in the diabetes-induced brosis of the heart, liver and kidney. 11,12 Diabetesinduced expression of TNF-a, IL-1b and IL-6 further promotes myocardial inammation, which leads to cardiac hypertrophy and brosis during the progression of cardiac remodelling.…”
Section: Introductionmentioning
confidence: 99%